Urban Growth and Sustainability in Abuja: The Role of Property Management - Abdulkareem, S. Y.; Ayuba, B.; Adamu, S.; Usman, M. K.; Kabir, D. M. (International Journal of Real Estate, 2026)
As urbanization intensifies, effective property management emerges as a crucial factor in ensuring the optimal use of land and built assets, maintaining environmental balance, and enhancing the quality of urban life. This study evaluates the role of property management in fostering urban growth and sustainability in Abuja, Nigeria's rapidly developing capital city. Using a mixed-method approach, the study draws on data from property managers, urban planners, estate developers, and regulatory authorities within Abuja. It investigates the relationship between professional property management and key urban sustainability indicators, including environmental preservation, efficient land use, socio-economic inclusivity, and infrastructure resilience. The findings reveal that well-managed properties contribute significantly to urban aesthetics, resource conservation, and investment confidence, which in turn drive sustainable development. However, challenges such as inadequate policy implementation, limited professional capacity, and weak enforcement of urban planning regulations hinder the full potential of property management in Abuja's urban landscape. The research concludes that property management is not merely a technical function but a strategic tool for achieving balanced urban growth and sustainability. The study recommends a more integrated framework where property managers play active roles in urban policy development, environmental planning, and community engagement. Strengthening professional standards, enhancing stakeholder collaboration, and implementing responsive regulatory mechanisms are essential to maximizing the impact of property management on Abuja’s urban future. This study provides valuable insights for policymakers, real estate professionals, and urban development stakeholders aiming to build more livable, resilient, and sustainable cities through efficient property management practices.
Keywords: Property management; Urban growth; Sustainability